Public health policy and political contestation in Indonesia - Cashtri Meher; Fotarisman Zaluchu (AOSIS, 2024)
Public health issues should be a focal concern for public leaders. A critical moment for articulating intended policies is during elections. At this time, candidates present significant ideas and proposals derived from the evaluation and reflection on the previous administration's governance. This approach ensures that the proposed programmes are grounded in evidence. In 2024, Indonesia conducted general elections, amid significant public health challenges such as the persistently high prevalence of stunting and poor maternal and child health outcomes. The Prabowo-Gibran, who then won the election, focused their campaign on providing free food and milk. This campaign appears to be unsupported by a comprehensive improvement plan, leading to the impression that public health issues are merely used to enhance electoral appeal.